Peningkatan Profesionalisme Guru Sekolah Dasar dalam Upaya Meningkatkan Mutu Pendidikan - Sugianto, Nanda Huda (Jurnal Administrasi Publik, 2013)
Abstract: Improvement profesionalism Elementary School Teacher In Effort to Improving the Quality Education. The central issue in regional development is the extent of the scope of regional development, one of which is in the field of education in accordance with the regulations of Law No. 32 of 2004, clause (14). Lack of professional teachers become problems in elementary school education. This study aims to analyze and describe the performance of the Regional Office of Education in the implementation of enhancing the professionalism of elementary school teachers in the Blitar city and the factors that affect the implementation of the professional development of primary school teachers. This research uses descriptive qualitative research approach. The results showed that the performance of the Regional Office of Education in the implementation of the professional development of primary school teachers in the city of Blitar quite well Factors supporting funding from the budget, the number of teachers and schools that are not too large and qualified personnel and given programâ€™s activities. Inhibiting factor funds and welfare of teachers, facilities and infrastructure, a gap of information between the results of the meeting with the principal and its delivery to a different teacher. The advice given provided sufficient budget to improving the welfare of teachers, departments should focus more on the fulfillment of facilities and infrastructure, intensive meetings with principals and teachers in order to avoid gaps in information. Keywords: human resource management, professional development of teachers, basic education Abstrak: Peningkatan Profesionalisme Guru Sekolah Dasar dalam Upaya Meningkatkan Mutu Pendidikan. Masalah pokok dalam pembangunan daerah adalah luasnya lingkup pembangunan daerah, dimana salah satunya adalah dibidang pendidikan sesuai dengan peraturan dalam Undang-Undang No. 32 tahun 2004 pasal (14). Kurangnya guru yang profesional menjadi permasalahan dalam penyelenggaraan pendidikan sekolah dasar. Penelitian ini bertujuan untuk menganalisis dan mendeskripsikan kinerja Dinas Pendidikan Daerah dalam pelaksanaan peningkatan profesionalisme guru sekolah dasar di Kota Blitar dan faktor-faktor yang mempengaruhi pelaksanaan peningkatan profesionalisme guru sekolah dasar. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan diskriptif. Hasil penelitian menunjukan bahwa kinerja Dinas Pendidikan Daerah dalam pelaksanaan peningkatan profesionalisme guru sekolah dasar di Kota Blitar cukup baik. Faktor pendukung sumber dana dari APBD, jumlah guru dan sekolah yang tidak terlalu besar dan aparat yang mumpuni dan diberikanya program kegiatan. Faktor penghambat dana dan kesejahteraan guru, sarana dan prasarana, terjadi kesenjangan informasi antara hasil rapat dengan kepala sekolah dan penyampaiannya kepada guru berbeda. Saran yang diberikan yaitu disediakan anggaran yang memadai bagi peningkatan kesejahteraan guru, dinas harus lebih fokus terhadap pemenuhan sarana dan prasarana, pertemuan yang intensif dengan kepala sekolah dan guru agar tidak terjadi kesenjangan informasi. Â  Kata kunci: manajemen sumber daya manusia, pembinaan profesionalisme guru, pendidikan dasar.